Templated Out‐of‐Equilibrium Self‐Assembly of Branched Au Nanoshells. Issue 12 (17th January 2023) - Marchetti, Alessandro; Gori, Alessandro; Ferretti, Anna Maria; Esteban, Daniel Arenas; Bals, Sara; Pigliacelli, Claudia; Metrangolo, Pierangelo
Abstract: Out‐of‐equilibrium self‐assembly of metal nanoparticles (NPs) has been devised using different types of strategies and fuels, but achieving finite 3D structures with a controlled morphology through this assembly mode is still rare. Here, a spherical peptide‐gold superstructure (PAuSS) is used as a template to control the out‐of‐equilibrium self‐assembly of Au NPs, obtaining a transient 3D‐branched Au‐nanoshell (BAuNS) stabilized by sodium dodecyl sulphate (SDS). The BAuNS dismantles upon SDS concentration gradient equilibration over time in the sample solution, leading to NPs disassembly and regression to PAuSS. Notably, BAuNS assembly and disassembly promotes temporary interparticle plasmonic coupling, leading to reversible and tunable changes of their plasmonic properties, a highly desirable behavior in the development of optoelectronic nanodevices. Abstract : Out‐of‐equilibrium self‐assembly of metal nanoparticles (NPs) achieving 3D structures with controlled morphology is still rare. Here, a peptide‐gold superstructure is used as template to control the out‐of‐equilibrium self‐assembly of Au NPs, obtaining a transient 3D‐branched Au‐nanoshell stabilized by a surfactant (SDS). The nanoshell dismantles upon SDS concentration gradient equilibration, leading to disassembly and regression to the template.